2016
DOI: 10.1155/2016/7340641
|View full text |Cite
|
Sign up to set email alerts
|

Topical Administration of Pirfenidone Increases Healing of Chronic Diabetic Foot Ulcers: A Randomized Crossover Study

Abstract: Only 30 percent of chronic diabetic foot ulcers heal after 20 weeks of standard treatment. Pirfenidone is a drug with biological, anti-inflammatory, and antifibrotic effects. The aim of this study was to evaluate the effect of topical pirfenidone added to conventional treatment in noninfected chronic diabetic foot ulcers. This was a randomized crossover study. Group 1 received topical pirfenidone plus conventional treatment for 8 weeks; after this period, they were switched to receive conventional treatment on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 16 publications
0
20
0
1
Order By: Relevance
“…A synthetic chemical, prifenidone (PFD), was found to modulate the expression of TNF-α, TGF-β, FGF, PDGF, and VEGF, giving it anti-fibrotic and anti-inflammatory properties. In two phase III clinical trials, topical PFD addition to conventional treatment significantly improved healing in DFUs [104,105].…”
Section: Non-endogenous Moleculesmentioning
confidence: 99%
“…A synthetic chemical, prifenidone (PFD), was found to modulate the expression of TNF-α, TGF-β, FGF, PDGF, and VEGF, giving it anti-fibrotic and anti-inflammatory properties. In two phase III clinical trials, topical PFD addition to conventional treatment significantly improved healing in DFUs [104,105].…”
Section: Non-endogenous Moleculesmentioning
confidence: 99%
“…The results of an early study with carboxymethylcellulose dressing suggesting that the intervention improved ulcer depth were not born out by a large outcome blind RCT . Two recent RCTs with topical Pirferidone (with potential anti‐inflammatory/antifibrotic properties) had methodological limitations; neither were blinded, results were analysed per protocol, and there was a high dropout rate in one, and an unexpectedly low healing rate in the control group in the other . Four RCTs of products designed to promote healing; Chitosan and Isosorbide dinitrate, hyaluronic acid, an acellular flowable matrix, and the proteolytic fraction from latex P1G10 provided little support for the use of these agents in clinical practice because of a small number of recruited patients, nonblinding, per protocol analysis, and/or high drop‐out rates.…”
Section: Recommendationsmentioning
confidence: 99%
“…While the exact mechanism(s) of PFD remain unknown, previous studies demonstrated its effectiveness at mitigating myofibroblast differentiation, proliferation, and profibrotic cytokine production in both in vitro and in vivo models of lung, liver, and renal fibrosis [22,23]. The potential of PFD as a topical therapeutic agent for use during wound healing [24,25] or following HTS development [26] has been suggested, however the mechanism by which PFD exerts its antifibrotic properties on dermal cells has not been fully described [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%